DJT: directionless jumping train - NDI, BILL F. (LANGAA RPCIG, 2021)
Through a careful allusive poetic composition process, the poet takes on the aberrant oppression that a mad egocentric individual at the helm of a train forces upon his passengers and not without their complicity, and who while boarding the train are fully aware the train is one of doom. The poem comes across as the poet's reconstruction of the wrong turn in world politics from the wreckage and random distemper of a particular irate ruler with neither political modicum/wit nor understanding of the true functioning of democracy. The poem memorializes the chaos and contemporizes America in a bid to arm the oppressed with the powerful weapon that is memory.